Microstructure and wear resistance of modified surfaces obtained by ion-plasma nitriding of 40ХН2МА steel - Smirnov, I.V.; Chornyi, A.V.; Lysak, V.V.; Kaplun, P.V.; Drobot, O.S.; Poberezhnyi, M.M.; Rutkovskyi, A.V. (Problems of Tribology, 2022)
The article is devoted to the analysis of wear resistance of diffusion coatings, which were applied by ionic nitriding on steel 40ХН2МА. There is a comparison of the technological efficiency of the results. The parameters of technological modes used in the process of application are presented, with the list of equipment and stages. The authors conduct the comparative analysis of chemical composition, microstructure, metallographic and tribological studies. They study the wear kinetics of 40ХН2МА steel with nitrided coatings as well as provide practical recommendations on the use of hardened samples in dry friction conditions.